Partisipasi Publik Digital dalam Praktik Humas Pemerintah: Studi pada Instagram @BLK_Kotatangerang - Zovan Kahfi; Siti Zulzilah; Shilvy Andini Sunarto; Widiastiana Vista Wijaya; Citra Puspa Maulidina (Asosiasi Dosen Muda Indonesia, 2026)
Social media has become a primary channel for government public relations practices in building public communication, yet few local government institutions have adopted public relations models that balance informative and dialogic approaches. This study aims to analyze the government public relations practices of the Balai Latihan Kerja (BLK) – the Vocational Training Center of Tangerang City – through its Instagram account @blk_kotatangerang in fostering digital public participation. BLK Kota Tangerang is a Technical Implementation Unit (UPT) under the Manpower Office that organizes competency-based vocational training to reduce unemployment rates. This research employs a qualitative descriptive method with a case study approach, utilizing the Excellence Theory and the Four Models of Public Relations (Grunig & Hunt, 1984) as analytical frameworks. The findings reveal that BLK Kota Tangerang's communication strategy applies a hybrid model, characterized by the dominance of one-way information dissemination (public information model) combined with creative approaches (press agentry model), as well as dialogic efforts (two-way symmetrical model) through polling features and responsive interactions to capture public aspirations. This study contributes as a reference for local government institutions in optimizing social media as a participatory and effective public communication tool. Keywords: Government Public Relations, Digital Public Participation, Excellence Theory, Four Models of Public Relations, Instagram